2021
DOI: 10.7759/cureus.19384
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations in Acute Leukemia Patients and Their Relation With Hematological Parameters in a Tertiary Care Center

Abstract: Background: Leukemia is a neoplastic disorder that affects blood and bone marrow and is characterized by white blood cells' abnormal proliferation. Leukemia patients may present with different ophthalmic manifestations. This study aims to provide an updated data about the prevalence and types of ocular manifestations in acute leukemia patients and their relation with the hematological parameters. Methods: This retrospective cross-sectional study included all acute leukemia patients diagnosed from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Nevertheless, PLT counts did not appear to be related. In previous research, some results were consistent with ours, but some differed ( 12 ). El-asrar et al found that patients with AML with Roth plaques had significantly higher WBC counts than did those without hemorrhage and that thrombocytopaenia was not associated with retinal hemorrhage ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, PLT counts did not appear to be related. In previous research, some results were consistent with ours, but some differed ( 12 ). El-asrar et al found that patients with AML with Roth plaques had significantly higher WBC counts than did those without hemorrhage and that thrombocytopaenia was not associated with retinal hemorrhage ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Immunosuppression caused by illness or its treatment, such as chemotherapy and bone marrow transplantation, can lead to opportunistic infections [6,7]. The overwhelming majority of patients with leukemia reported in our survey involved retinal hemorrhages (65%), similarly described in Bukhari et al retrospective cross-sectional study including 81 acute leukemia patients, with 60% of patients presenting ocular manifestations [8]. Male showed a greater predisposition, possibly due to the protective effect of estrogen in women against retinopathy [9].…”
Section: Discussionsupporting
confidence: 65%
“…4 This is consistent with the paper of Koshy et al 2 Very recently, Bukhari et al published their retrospective data on all included acute leukemia patients who underwent an ophthalmic examination during a period from 2015 to 2020. 5 They concluded that it is highly preferable to examine acute leukemia patients routinely before, during, and at the end of treatment to prevent serious ocular damage and to monitor the disease course.…”
Section: E T T E R T O T H E E D I T O R Comment On: Ocular Abnormali...mentioning
confidence: 99%